The First Mitochondrial Genome for Geastrales (Sphaerobolus stellatus) Reveals Intron Dynamics and Large-Scale Gene Rearrangements of Basidiomycota - Ye, Jinghua; Cheng, Jie; Ren, Yuanhang; Liao, Wenlong; Li, Qiang (Frontiers in Microbiology, 2020)
In this study, the mitogenome of artillery fungus, Sphaerobolus stellatus, was assembled and compared with other Basidiomycota mitogenomes. The Sphaerobolus stellatus mitogenome was composed of circular DNA molecules, with a total size of 152,722 bp. Accumulation of intergenic and intronic sequences contributed to the Sphaerobolus stellatus mitogenome becoming the fourth largest mitogenome among Basidiomycota. We detected large-scale gene rearrangements in Basidiomycota mitogenomes, and the Sphaerobolus stellatus mitogenome contains a unique gene order. The quantity and position classes of intron varied between 75 Basidiomycota species we tested, indicating frequent intron loss/gain events occurred in the evolution of Basidiomycota. A novel intron position classes (P1281) was detected in the Sphaerobolus stellatus mitogenome, without any homologous introns from other Basidiomycota species. A pair of fragments with a total length of 9.12 kb in both the nuclear and mitochondrial genomes of Sphaerobolus stellatus was detected, indicating possible gene transferring events. Phylogenetic analysis based on the combined mitochondrial gene set obtained well-supported tree topologies (bayesian posterior probabilities ≥ 0.99; bootstrap values ≥ 98). This study served as the first report on the mitogenome from the order Geastrales, which will promote the understanding of the phylogeny, population genetics, and evolution of the artillery fungus, Sphaerobolus stellatus.